Learning Design: To Improve Mathematical Problem-Solving Skills Using a Contextual Approach (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Mathematical problem-solving skills are essential for success in various fields, including science, technology, engineering, and mathematics (STEM). However, many students struggle with math and often lack the necessary skills to solve problems effectively. Traditional math education often lacks real-world context, which makes it difficult for students to engage with the material and develop problem-solving skills. To address this issue, the need for a contextual approach to learning design to improve mathematical problem-solving skills is inevitable. In the context of math education, this approach can be applied by providing learners with mathematical problems that are embedded in meaningful contexts, such as real-world scenarios or case studies. This approach draws from theories such as situated cognition and social constructivism, which emphasize the importance of considering the broader context in which problem-solving occurs. A literature review is used in this research method, and data analysis is done descriptively. By applying a contextual approach to mathematics learning design, students are expected to develop mathematical problem-solving skills that are important for success in various fields.